Tinjauan Pustaka Terbaru Peran Omega 3 Pada Dry Eye - Anugrahsari, Santi; Lesmana, Andri; Korwa, Daniela Dirgantari; Kumala Sari, Ni Putu Winda (Universitas Kristen Krida Wacana, 2025)
Dry eye disease (DED) or dry eye disease is a common condition in every country. Dry eyes can cause symptoms such as discomfort or a cycling sensation, red eyes and a feeling of blockage. Inflammation is one of the underlying pathophysiology of dry eyes. One of the therapeutic approaches that has received major attention is the use of omega-3 fatty acid supplements, which are known to have anti-inflammatory properties and can support eye health. Recent studies have shown that omega-3, especially EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid), can improve tear quality, improve meibomian gland function, and increase tear production in people with dry eyes. In addition, omega-3 also plays a role in reducing symptoms of dry eyes, although several studies have shown significant results, but the effectiveness of omega-3 in managing dry eyes still requires further research, especially in determining the optimal dose and duration of therapy. This literature review aims to review the latest developments related to the role of omega-3 in dry eye therapy and explore the underlying effects of omega-3 on dry eyes. Further research is expected to provide stronger evidence regarding the role of omega-3 in dry eye therapy.